PENINGKATAN INTENSI LOYALITAS WISATAWAN MELALUI PENGALAMAN BERWISATA CILETUH-PALABUHANRATU UNESCO GLOBAL GEOPARK - Riski Taufik Hidayah; Eristy Minda Utami (Jurnal Riset Entrepreneurship, 2023)
Ciletuh-Palabuhanratu UNESCO Global Geopark (CPUGGp) has become the pride of the people of West Java because of its natural wealth, biological wealth, and community-cultivated wealth that creates tourism experience that never found in other touristarea. However, the level of tourist visits has continued to decreasesince the establishment of UNESCO Global Geopeark Ciletuh-Palabuhanratu status has been held on 17 April 2018. This situation deserves attention considering that the presence of Geopark should be able to improve the economy of people who live in the tourist area. The purpose of this research isto ascertain how the tourism experience can affect the loyalty intention of CPUGGP. The implication of this research is expected to be a reference for the Geopark Ciletuh management in order to develop Geopark as a tourist area that can provide economic benefits for the local community. The research method used is verification with tourists visiting CPUGGp in 2020 as research population. This study used Spearman rank correlation, coefficient of determination, and t-test with a significance level of 5% in conducting data analysis. This study found that there is an influence of tourism experience on loyalty intention of 75,2%